Customer Perception Of Results System In Bank Muamalat Kcp Curup - Azuwandri Azuwandri; By Kasdi (UNIVED Press, 2023)
iB Muamalat Regular Savings has a low-cost savings concept, apart from not being subject to customer administration fees, cash withdrawals are also free of charge and a very profitable profit-sharing system. The purpose of this study was to determine customer perceptions of the profit-sharing system for the iB Muamalat Regular savings product at Bank Muamalat KCP Curup . The data collection method used a questionnaire on 60 customers who had iB Muamalat savings at Bank Muamalat KCP Curup. The analytical method used is rating scale analysis. Based on the results of the study, the average respondent's assessment of customer perceptions of the profit sharing system at Bank Muamalat KCP Curup was 249.83 with the rating criteria agreeing. This means that customers agree that internal factors and external factors will influence customer perceptions of the profit-sharing system assessment applied to iB Muamalat Regular savings at Bank Muamalat KCP Curup. Internal factors are the highest of the factors that influence customer perceptions of the profit sharing system that exists at Bank Muamalat KCP Curup. Because internal factors are factors that come directly from within the customer External factors are the lowest factors because a customer considers the profit sharing applied by Bank Muamalat KCP Curup to their value not because of the influence of other people.